2014
DOI: 10.1177/1933719113508815
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Invasion and Blood Vessel Remodeling Are Altered in a Rat Model of Lifelong Maternal Obesity

Abstract: Maternal obesity is associated with an increased risk of a number of pregnancy complications, including fetal demise, which may be linked to impaired placental development as a result of altered trophoblast invasion and vessel remodeling. Therefore, we examined these parameters in pregnant rats fed a control (normal weight) or high fat (HF) diet (obese) at 2 critical times of rat placental development. Early trophoblast invasion was increased by approximately 2-fold in HF-fed dams with a concomitant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 63 publications
(108 reference statements)
5
42
1
1
Order By: Relevance
“…Importantly, we show that obesity‐related uterine vascular changes coincide with fewer uNK and altered global uNK gene expression . These findings are consistent with rodent data showing that high‐fat diet exposure prior to and during pregnancy leads to impaired uterine artery remodeling . Notably, vascular defects of this type are also observed in rats and mice deficient in uNK .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, we show that obesity‐related uterine vascular changes coincide with fewer uNK and altered global uNK gene expression . These findings are consistent with rodent data showing that high‐fat diet exposure prior to and during pregnancy leads to impaired uterine artery remodeling . Notably, vascular defects of this type are also observed in rats and mice deficient in uNK .…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, the outcome of increased uNK activity resulting from obesity most likely affects uterine vascular remodeling and angiogenesis. Although our study does not examine this, prior studies showing impaired blood vessel remodeling in rodents subjected to high‐fat diets and in obese pregnant women indicate that these vascular defects may be due to obesity‐directed changes in uNK function. Further work is required to decipher these interactions.…”
Section: Discussionmentioning
confidence: 80%
“…Obese women are about 3 times more likely to develop major complications during pregnancy, such as gestational diabetes or preeclampsia, and excess adiposity increases the risk of preterm birth, which is responsible for ~75% of the 4 million neonatal deaths annually worldwide (3,4); these disorders likely result from placental dysfunction (5). Studies using animal models have confirmed a role for obesity in causing placental dysfunction defined in part by altered vascular changes within the fetal-maternal environment (6,7). However, the underlying mechanisms linking obesity to poor pregnancy outcomes are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 More recently the rat has gained favor as a model of trophoblast invasion as it confers several advantages over the mouse in that the depth of trophoblast invasion follows a similar pattern to that observed in the human and trophoblasts also colonize the spiral arteries and contribute to their remodeling. [6][7][8] Finally, animal models allow the complex in vivo interactions between the trophoblast and endometrium to be examined, an aspect of trophoblast invasion that is particularly difficult to accurately replicate in vitro. Despite these advantages, it is important to remember that rodent placentation is anatomically distinct from human placentation, and thus it is important to relate findings from such animal models back to human trophoblast.…”
Section: Introductionmentioning
confidence: 99%